Militanza e creatività nella pluralità dei borderscapes. Produzione estetica di frontiera tra il Mediterraneo e il nord del Messico - Andrea Buchetti (Archivio Antropologico Mediterraneo)
In a contemporaneity dominated by a prevailing visual culture, there is an urgent need to rethink how forms of resistance and cultural creativity are articulated according to such lexicons. Borders offer a privileged context in which to observe the social construction of particular aesthetics. Can we adopt the concept of borderscape to approach the plurality of imaginaries that borders stimulate between militant voices and autochthonous self-representations? Is it possible to identify third spaces of creativity that share symbols and identity repertoires between the local and the global? By attributing to aesthetics varying degrees of agency, drawing on navigations in the Sicilian Channel with the Ermenautica project, I analyze how interventions and ideologies emerge with extreme similarity between the Mediterranean Sea and the U.S.-Mexico border, proposing a movement between sea and land through a sensitivity to the cultural vitality of border spaces.